Social Representations of the Africentric School as Portrayed Through the Toronto Newspapers - Laflamme-Lagoke, Mobolaji; Negura, Lilian (Canadian Journal of Counselling and Psychotherapy, 2014)
<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-CA; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-size: 11.0pt; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi;">In 2007, the Toronto District School Board announced a proposal to open an Africentric public elementary school, which would bring to the fore the experience and knowledge of people of African and Caribbean descent. This proposed project led to a debate in the Canadian media, with public opinion being divided between supporters of the proposal and those who opposed it. This article presents a study of the social representations of the Africentric school conveyed by the Toronto newspapers as they covered this debate. Through thematic content analysis, two different social representations of the Africentric school were identified, the main elements of which were the idea of segregation and the empowerment of the Black community.